(untitled) (Research, Society and Development, 2021)
Introduction: Fibromyalgia is characterized by musculoskeletal manifestations of chronic, lasting, diffuse pain, with the presence of specific pain points and the absence of tissue inflammation. Its chronic aspect is closely related to mood changes, in a way that it establishes a bidirectional link with depression, based on the activation of brain neural patterns that increase the sensation of pain. Therefore, depression is one of the most prevalent psychiatric comorbidities of fibromyalgia, with a high prevalence rate. Objective: To analyze national and international scientific publications in the field of public health, aiming to understand the manifestations of depression symptoms in patients with fibromyalgia. Methodology: This is a systematic literature review using the following databases: SCIELO, LILACS, MEDLINE and PUBMED. The descriptors used for data collection were: Fibromyalgia; Depression; Chronic pain. The inclusion criteria were only articles that address the topic in question, full text, found in Portuguese, English and Spanish in the last 5 years. Results: According to the results obtained, patients who have fibromyalgia have a high rate of depression. The prevalence of depression in patients with fibromyalgia ranges from 50.5% to 80%. Conclusion: Given the complexity of depression assessment, more research is needed to verify more reliable results, as well as characteristics, the influence of non-physical factors on intensity and prevalence, and the best treatment that meets the needs of patients.